Decentralised Policing System and Insecurity in Nigeria: An Opinion Survey of Residents of Ovia North East Local Government Area, Edo State - Okojie , Theophilus Arebamen; Iyere, Prosper Onono (Kashere Journal of Politics and International Relations, 2025)
The study explored the opinions of the people of the Ovia Northeast Local Government, Edo State, regarding the increasing public opinion on decentralising the security system in Nigeria. The study was anchored on concentric circle theory that postulates that security management should begin from the community level, to the state level and the federal level for effective results. A sample of 400 residents of the Local government Area was obtained, and 352 questionnaires were returned. The data obtained were analysed with simple percentages, the mean and the standard deviation. The study found that respondents supported the creation of a state policing system backed by law in Nigeria; believe there will be no security implications for having state police because they believe that state actors will not hijack state police, collude with criminals to perpetrate crimes, use guns to steal from people or extort people; and believe that state police will be effective in tackling insecurity because they will work in the interest of the people rather than the Nigerian government. Based on these findings, the study, therefore, recommends that the National Assembly should amend the 1999 Constitution to accommodate the state policing system.